Iris‐based continuous authentication in mobile ad hoc network. (28th October 2019) - Ramkumar, D.; Annadurai, C.; Nelson, I.
Summary: Mobile Ad hoc Networks (MANETs) are temporary in nature, with security concerns being more vulnerable than the other types of networks. Most of the works concentrate on either authentication or intrusion detection. This framework considers both intrusion detection and authentication continuously. It has been done for different layers of security for finding the intruder and eliminate from the network. Iris images have been used in this work for the purpose of authentication. Detection and response engines have been used for intrusion detection and high security in ad hoc network. The simulation results clearly show the iris‐based continuous authentication detecting most of the intruders and eliminates from the network.